Royal Entomological Society Book of British Insects - Barnard, Peter C.; Wiley InterScience (Online service) (Chichester ; New York : Wiley-Blackwell, 2011)
The Royal Entomological Society (RES) and Wiley-Blackwell are proud to present this landmark publication, celebrating the wonderful diversity of the insects of the British Isles, and the work of the RES (founded 1833). This book is the only modern systematic account of all 558 families of British insects, covering not just the large and familiar groups that are included in popular books, but even the smallest and least known. It is beautifully illustrated throughout in full colour with photographs by experienced wildlife photographers to show the range of diversity, both morphological and behavioural, among the 24,000 species. All of the 6,000 genera of British insects are listed and indexed, along with all the family names and higher groups. There is a summary of the classification, biology and economic importance of each family together with further references for detailed identification. All species currently subject to legal protection in the United Kingdom are also listed. The Royal Entomological Society is one of the oldest and most prestigious of its kind in the world. It is the leading organisation for professional entomologists and its main aim has always been the promotion of knowledge about insects. The RES began its famous Handbooks for the Identification of British Insects in 1949, and new works in that series continue to be published. The Royal Entomological Society Book of British Insects has been produced to demonstrate the on-going commitment of the RES to educate and encourage each generation to study these fascinating creatures. This is a key reference work for serious students of entomology and amateur entomologists, as well as for professionals who need a comprehensive source of information about the insect groups of the British Isles they may be less familiar with.
Entognatha. Part Introduction -- Order Collembola: The springtails -- Order Diplura: The Two-Tailed or Two-Pronged Bristletails -- Order Protura: The Proturans -- Insecta-'Apterygota'. Part Introduction -- Order Archaeognatha or Microcoryphia: The Bristletails -- Order Zygentoma: The Silverfish and Firebrats -- Palaeoptera. Part Introduction -- Order Ephemeroptera: The Mayflies or Upwing Flies -- Order Odonata: The Dragonflies and Damselflies -- Polyneoptera. Part Introduction -- Order Dermaptera: The Earwigs -- Order Dictyoptera: The Cockroaches, Termites and Mantids -- Order Orthoptera: The Grasshoppers, Crickets and Bush-Crickets -- Order Phasmida: The Stick-Insects -- Order Plecoptera: The Stoneflies -- Paraneoptera. Part Introduction -- Order Hemiptera: The True Bugs -- Order Phthiraptera: The Sucking and Biting Lice -- Order Psocoptera: The Booklice and Barklice -- Order Thysanoptera: The Thrips -- Endopterygota. Part Introduction -- Order Coleoptera: The Beetles -- Order Diptera: The True Flies -- Order Hymenoptera: The Ants, Bees and Wasps -- Order Lepidoptera: The Butterflies and Moths -- Order Mecoptera: The Scorpionflies -- Order Megaloptera: The Alderflies -- Order Neuroptera: The Lacewings -- Order Raphidioptera: The Snakeflies -- Order Siphonaptera: The Fleas -- Order Strepsiptera: The Stylops -- Order Trichoptera: The Caddisflies or Sedge Flies -- Index to all Names of Insect Genera, Families and Higher Taxa in the UK.
Includes bibliographical references and index.
Print version record.
Keywords: Insects -- British Isles -- Identification; Insects; Europe -- British Isles; Electronic resource; Electronic books; Guidebooks